Sejarah Tradisi Khitbah Dalam Islam dan Adat Indonesia - Misbachul Fitri, Abd. Basit; Miftakhuddin , Mukhammad (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2025)
Khitbah (marriage proposal) constitutes an initial stage that holds an important position in the process of marriage, both from the perspective of Islamic law and in the practice of customary law in Indonesia. This article aims to examine the concept, legal basis, principles, and procedures of khitbah in Islam, while also exploring the history and variety of khitbah traditions within several Indonesian customary systems, such as Javanese, Minangkabau, Bugis-Makassar, Batak, and Sundanese customs. The study employs a library research method with normative and historical approaches, through analysis of sources from the Qur’an, Hadith, scholarly opinions, the Compilation of Islamic Law, as well as literature on customary law and legal anthropology. The findings indicate that khitbah in Islam has a clear legal foundation, with its original ruling being permissible (mubāḥ), which may change depending on circumstances, and is regulated by conditions, rights, and limitations intended to safeguard the interests of all parties involved. Meanwhile, the practice of khitbah in Indonesian customary law demonstrates diverse forms and procedures, yet essentially serves the same purpose: expressing serious intent toward marriage and fostering kinship relations between families. This article concludes that there is a strong harmonization between Islamic legal provisions and customary law in the practice of khitbah in Indonesia, reflecting the flexibility of Islamic law in adapting to local socio-cultural contexts without abandoning its fundamental principles.